2012
DOI: 10.1124/mol.112.079293
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotonic Steroids Stabilize Regulator of G Protein Signaling 2 Protein Levels

Abstract: Regulator of G protein signaling 2 (RGS2), a G q -specific GTPase-activating protein, is strongly implicated in cardiovascular function. RGS2(Ϫ/Ϫ) mice are hypertensive and prone to heart failure, and several rare human mutations that accelerate RGS2 degradation have been identified among patients with hypertension. Therefore, pharmacological up-regulation of RGS2 protein levels might be beneficial. We used a ␤-galactosidase complementation method to screen several thousand compounds with known pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 60 publications
4
43
2
Order By: Relevance
“…Strategies to target regulation of RGS protein expression have focused on post-translational mechanisms that control protein stability (Sjögren et al, 2012;Raveh et al, 2014). In contrast, our data suggest predominantly transcriptional regulation of Rgs10 expression.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Strategies to target regulation of RGS protein expression have focused on post-translational mechanisms that control protein stability (Sjögren et al, 2012;Raveh et al, 2014). In contrast, our data suggest predominantly transcriptional regulation of Rgs10 expression.…”
Section: Discussioncontrasting
confidence: 55%
“…Given the ability of RGS10 to regulate inflammatory signaling, understanding the mechanisms that control RGS10 levels in microglia may reveal new therapeutic strategies to address neuroinflammatory disease. The most commonly described mechanism for regulation of RGS protein abundance involves critical post-translational mechanisms that control protein stability (Sjögren et al, 2012;Raveh et al, 2014). However, our studies in ovarian cancer cells suggest that Rgs10 is transcriptionally regulated by DNA and histonetargeted epigenetic mechanisms (Ali et al, 2013;Cacan et al, 2014).…”
Section: Introductioncontrasting
confidence: 43%
“…Low RGS2 protein levels are associated with hypertension and other cardiovascular pathologies (Heximer et al, 2003;Takimoto et al, 2009;Tsang et al, 2010) and could also be involved in the progression of prostate and breast cancer (Cao et al, 2006;Lyu et al, 2015). In our initial screen, we identified digoxin and other cardiotonic steroids as selective stabilizers of RGS2 protein levels (Sjögren et al, 2012). In subsequent work, we demonstrated that digoxin is protective in a murine model of cardiac injury, an effect that was lost in RGS2 À/À mice (Sjögren et al, 2016b).…”
Section: Advances In Rgs Protein Drug Discovery -From Biochemical Actmentioning
confidence: 99%
“…Several RGS proteins are downregulated during pathological insults so finding ways to increase their expression, and thereby function, is an attractive alternative strategy to achieve this goal. This encouraged us to develop a cell based enzyme complementation assay to screen for small molecule stabilizers of RGS2 (Sjögren et al, 2012;Raveh et al, 2014). As discussed above, RGS2 is one of several RGS proteins that is rapidly degraded through the ubiquitin-proteasomal pathway.…”
Section: Advances In Rgs Protein Drug Discovery -From Biochemical Actmentioning
confidence: 99%
“…Finally, RGS2 expression was also found to be increased in patients with Bartter's/Gitelman's syndrome, a disorder characterized by low blood pressure (Calò et al, 2004). RGS2 protein levels are highly regulated by proteasomal degradation (Bodenstein et al, 2007;Sjögren et al, 2012). This rapid degradation of RGS2 and other RGS proteins by proteasomal mechanisms provides a useful control point at which to pharmacologically modulate RGS levels and function .…”
Section: Introductionmentioning
confidence: 99%